Pembagian Daya Dari Beberapa Solar Panel Menggunakan PID - Madani, Hayrul; Dwiyanti, Dika; Andik Setiawan, I Made; Surojo, Surojo (Jurnal Inovasi Teknologi Terapan, 2023)
Photovoltaic power plants have drawbacks, one of which is that it is very dependent on the ntensity of sunlight and the surface temperature of the solar panels. In this case it takes a battery to be able to cope with photovoltaic at night.The battery has a function as a means of storing electrical power generated by photovoltaic and supplying power to the load. Therefore, we need a tool that ican regulate the power generated from several solar panels to fulfill the required load power.n this test the Arduino Mega2560 icontrol device was used with the PID control method as the brain of the design that regulates the output power of the solar panel so that it remains stable in fulfilling the load power. From the results of this test, the results show that this tool can share power and regulate ipower ias needed with pid control using the Trial and Error method in each solar panel with a percentage of 60% and 40% in stable power with set point i 1 14V and set point 2 10V with.the maximum power of 10mW obtained from each solar panel is then used as a graph ifrom ithe test results.